INTRODUCTION OF DRYING AND PACKAGING TECHNOLOGY IN BALINGKA VILLAGE, AGAM DISTRICT, WEST SUMATRA PROVINCE - Ekaputra, Eri Gas; Wellyanalina, Wellyanalina; Abdi, Abdi; Ramadani, Siska Fitri (Andalasian International Journal of Social and Entrepreneurial Development, 2022)
Abstract Background: the activity was carried out with the aim of introducing and training the people of NagariBalingka regarding the role of drying and packaging technology for local food in the Nagari to become products that have more value and can support the economy of the people there. Methods: Drying and packaging techniques were introduced through verbal explanations while being practiced directly by the agricultural technology faculty team, Andalas University. Conclusion: the information presented can be an alternative/solution for local food processing in Balingka Village into more valuable products such as chili powder and carrot chips. This can be a new breakthrough for community groups there to further explore processed products with drying techniques as innovative and superior products from their village